Implicit Attitudes to Female Body Shape in Spanish Women With High and Low Body Dissatisfaction - Hernández-López, Mónica; Antequera-Rubio, Alba; Rodríguez-Valverde, Miguel (Frontiers in Psychology, 2019)
Research on implicit attitudes to body image has grown substantially in recent years. The extant evidence reveals an implicit weight bias in the general population that has generally been interpreted in terms of anti-fat attitudes. However, research with the Implicit Relational Assessment Procedure (IRAP) shows that this bias appears to be driven by pro-slim rather than anti-fat implicit attitudes. Besides, the only IRAP study of this sort conducted in Spain found no evidence of such implicit weight bias (with similarly positive attitudes to thinness and fatness). Given the existing differences in body dissatisfaction (BD) among diverse cultural contexts, we wondered whether discrepancies in findings about implicit weight bias might be related to differences in BD amongst the samples in the different studies. This study explores whether women with extreme scores in BD (High vs. Low) show different patterns of attitudes to female body shape. Spanish female college students with extreme scores in the Body Shape Questionnaire (BSQ: high ≥ 104, percentile 80; low ≤ 52, percentile 20) completed an IRAP with pictures of overweight and underweight women as target stimuli and the words pleasant and unpleasant as labels. Participants also completed explicit ratings to the same stimuli and clinically relevant measures of body image related distress. Results showed an implicit weight bias only for women high in BD. While both groups showed equally positive implicit attitudes to thinness, only women with low BD showed implicit positive attitudes to fatness (and hence no bias). In turn, both groups presented a clear pro-thin/anti-fat explicit bias with positive ratings for underweight pictures and negative ratings for overweight pictures. The latter were stronger for the high BD group. Therefore, between-group differences were mainly driven by differences in attitudes to fatness (both implicit and explicit). Both implicit and explicit attitudes to fatness independently predicted eating disorders symptoms and other clinically relevant measures. These results are discussed in terms of their clinical implications.